Network as information: endogenous network in coordination game - Bo Wang; Suli Zheng (Journal of Applied Economics)
We investigate the concept of endogenous information leadership within the financial market. Prior to coordinating their investments, investors establish a star network at a certain cost. The central node of this star network functions as an information leader, collecting and sharing information with all network members, thereby enhancing the chances of successful coordination. We delve deeper into the process of selecting the information leader by introducing a name market, inspired by Tadelis (1999), to identify individuals with the highest leadership potential to assume this role. The interplay between leadership selection through the name market and successful coordination creates a reinforcing loop. The emergence of contagion is attributed to leadership dynamics. Furthermore, we identify an equilibrium where leadership alternates. Our findings provide new insights into the regulation of social media platforms.